1994
DOI: 10.1128/aac.38.7.1651
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial of fusidic acid for lepromatous leprosy

Abstract: Fusidic acid was assessed for antileprosy activity in nine lepromatous leprosy patients. Patients received fusidic acid at either 500 mg/day for 12 weeks or 750 mg/day for 4 weeks followed by 500 mg/day for 8 weeks. All patients showed time-dependent clinical improvement and decreases in bacillary morphological index, radiorespirometric activity and PCR signal, and in serum phenolic glycolipid I. Fusidic acid appears to be a weakly bactericidal antileprosy agent which may have a role in the multidrug treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…Earlier studies have shown that PCR positivity associated with M. leprae from skin biopsies from patients receiving successful anti-leprosy therapy was reduced significantly as early as 2 months after initiating therapy. 11,18 Similarly, in our study, successful treatment of MB patients for 1 year showed reductions in PCR reactivity from both sites sampled, suggesting that neither nasal secretions nor skin are likely portals of exit for M. leprae from patients receiving appropriate therapy. Earlier time points, ranging from 1 to 3 months, showed minor reductions in PCR positivity rates from both skin washings and nasal secretions.…”
Section: Discussionsupporting
confidence: 57%
“…Earlier studies have shown that PCR positivity associated with M. leprae from skin biopsies from patients receiving successful anti-leprosy therapy was reduced significantly as early as 2 months after initiating therapy. 11,18 Similarly, in our study, successful treatment of MB patients for 1 year showed reductions in PCR reactivity from both sites sampled, suggesting that neither nasal secretions nor skin are likely portals of exit for M. leprae from patients receiving appropriate therapy. Earlier time points, ranging from 1 to 3 months, showed minor reductions in PCR positivity rates from both skin washings and nasal secretions.…”
Section: Discussionsupporting
confidence: 57%
“…The rationale for testing CLARI, MINO, OFLO, and SPFX in clinical trials derived from their promising bactericidal effects in mice. Fusidic acid probably is the only drug which was said to be inactive against M. leprae in mice but exhibited a weak bactericidal activity against M. leprae in a human trial (7); nevertheless, its inactivity in mice has not been documented by the investigator and has yet to be confirmed by others. On the other hand, because the pharmacokinetics of the drugs and the pathogenesis of M. leprae infection in mice are quite different from those in patients, the potential lead of a new drug or a new treatment identified in the mouse footpad system must be evaluated in clinical trials before moving toward field application.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the cumbersome nature of this drug screening method, comprehensive estimates of drug resistance in leprosy have been difficult to obtain. A widely used indirect measure of drug‐resistant M. leprae is the radiometric analysis [3,4]. This method also has many disadvantages with regard to time, expense, and characterization of resistant mechanism for anti‐leprosy drug.…”
Section: Introductionmentioning
confidence: 99%